1970
DOI: 10.1017/s0043174500077250
|View full text |Cite
|
Sign up to set email alerts
|

Picloram Enhances 2,4-D Movement in Field Bindweed

Abstract: Field bindweed (Convolvulus arvensisL.) was sprayed with a mixture of (2,4-dichlorophenoxy)acetic acid (2,4-D) and 4-amino-3,5,6-trichloropicolinic acid (picloram). A mixture of picloram and 2,4-D each at 0.01 lb and 0.001 lb/A killed tops of plants faster than 2,4-D alone or picloram alone at the same rates. Higher rates of 1 lb/A picloram plus 1 lb/A 2,4-D and 0.1 lb/A picloram plus 0.1 lb/A 2,4-D were not consistently synergistic or antagonistic. The percent of plants which produced new growth were 0 for pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Agbakoba and Goodin (1970) also observed even distribution of 14 C-2, 4-D in field bindweed apical meristem and root tissue, similar to aminocyclopyrachlor. Much higher accumulation of 14 C-picloram in the apical meristems was found compared with the roots (Agbakoda and Goodin 1970). However, radioactivity was reported as the specific activity for each plant part on a fresh weight basis, so again, direct comparisons with the aminocyclopyrachlor translocation data from this study are difficult to make.…”
Section: Resultsmentioning
confidence: 67%
“…Agbakoba and Goodin (1970) also observed even distribution of 14 C-2, 4-D in field bindweed apical meristem and root tissue, similar to aminocyclopyrachlor. Much higher accumulation of 14 C-picloram in the apical meristems was found compared with the roots (Agbakoda and Goodin 1970). However, radioactivity was reported as the specific activity for each plant part on a fresh weight basis, so again, direct comparisons with the aminocyclopyrachlor translocation data from this study are difficult to make.…”
Section: Resultsmentioning
confidence: 67%
“…With intact plants absorption of 2,4-D was slightly enhanced by dicamba, while absorption of dicamba was stimulated in one experiment but not another. Agbakoba & Goodin (1970) found that absorption of 2,4-D was not affected by picloram but the uptake of picloram was reduced by 2,4-D in field bindweed (Convolvulus arvensis).…”
Section: Additivesmentioning
confidence: 94%
“…Long & Basler (1974) have also reported that 2,4,5-T enhances the translocation of 2,4-D in beans {Phaseolus vulgaris) and that 2,4-D does not promote the translocation of 2,4,5-T. The interaction between picloram and 2,4-D in field bindweed {Convolvulus arvensis) was examined by Agbakoba & Goodin (1970). They found that picloram increased the amount of 2,4-D translocated to untreated parts ofthe plant, while 2,4-D had no effect on overall picloram translocation.…”
Section: Additivesmentioning
confidence: 99%
“…Binning, Penner, and Meggitt (1971) found that a 7-day pretreatment with the ethylene-releasing compound, 2chloroethylphosphonic acid, enhanced basipetal transport of l4C-dicamba in wild garlic. Agbakoba and Goodin (1970) reported the effect of picloram on transport of 2,4-D in field bindweed; transport to the roots was not affected but picloram did appear to enhance upward movement of 2,4-D in the shoots. Although synergistic effects of combinations of herbicides are known, enhanced toxicity has not yet been shown to be a result of enhanced transport to the roots.…”
mentioning
confidence: 97%